The Interplay of Financial Literacy, Financial Inclusion, and Risk-Taking on MSME Performance - Sulistiono, Agus; Bayu, Muhammad; Munawaroh, Siti; Rudianto, Pandef (MES Management Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving national economic growth, making efforts to improve their performance crucial. This study, conducted on MSME actors in Tanjung Redeb District using the Structural Equation Modeling (SEM) approach, shows that financial literacy and financial inclusion are the main factors influencing MSME performance. These two aspects not only encourage business owners to be more willing to take calculated risks but also strengthen their ability to manage capital, plan their businesses, and innovate in the face of business challenges. This finding confirms that increased financial literacy and inclusion have both direct and indirect impacts on optimizing MSME performance through healthier and more strategic risk-taking. Therefore, the results of this research can serve as a reference for MSME actors to continue developing their financial competencies through training and utilizing various sources of information, both from financial institutions, the government, and digital platforms, to strengthen competitiveness and maintain business sustainability amidst increasingly dynamic competition.